Effect of allisartan on blood pressure and left ventricular hypertrophy through Kv1.5 channels in hypertensive rats. (3rd April 2022) - Xu, Chunfang; Zhao, Ziying; Yuan, Wang; Fengping, Zhao; Zhiqiang, Yan; Xiaoqin, Zhang
ABSTRACT: Background: The objective of the present work was to study the anti-hypertensive effect of allisartan on blood pressure (BP) and in facilitating left ventricular remodeling through voltage-gated potassium channels (Kv) 1.5 channels. Methods: A total of 30 SD rats were randomly divided into sham operation group, hypertension control group, and allisartan treatment group. Hypertension was induced by renal artery stenosis. The animals of treatment group were administered with allisartan once a day at a dose of 30 mg/kg body weight through an oral gavage for 4 weeks. The heart function of animals post 4 weeks of treatment was evaluated by echocardiography, and the degree of ventricular hypertrophy and cardiomyocyte hypertrophy were evaluated by histomorphology. The expression of Kv1.5 is detected by real-time quantitative polymerase chain reaction while Western blotting was used to detect the protein expression. Results: Four weeks after renal artery stenosis, a significant difference was observed in the whole heart ratio, left heart ratio, and cardiomyocyte area between allisartan treatment group and the hypertension control group ( P < .01). A significant decrease in BP of allisartan treatment group compared to hypertension control group ( P < .01) was observed. The expression of Kv1.5 mRNA was increased significantly ( P < .01) in allisartan treatment group compared to hypertension control group. Western blot analysis also confirmed the increased expression of Kv1.5 channel. Conclusion: The results showed that allisartan lowers BP and improves left ventricular remodeling through increased expression of Kv1.5 mRNA.